Pemberdayaan Kader Posyandu Tentang Praktik Pembuatan MPASI-Lokal ”Ikan Kembung Como” di Wilayah RW021 Serua-Ciputat : Indonesia - Mulyani, Erry Yudhya; Sari, Yumelda; Widiastuti, Mariyana (UII, 2024)
Based on SSGI 2022 data, the prevalence of stunting in Indonesia is 21.6% and in the South Tangerang city area in 2023 it is 9.0%. This figure is still above the government's target. One effort that can be made is by utilizing local food to improve the nutritional status of children under five. This activity is an educational program through training in making local MPASI biscuits made from